EFEKTIVITAS PENERAPAN MANAJEMEN TENAGA KEPENDIDIKAN DI MAN PANGKEP KABUPATEN PANGKEP - Muh Nur Islam Nurdin (Educational Leadership: Jurnal Manajemen Pendidikan, 2023)
This study aims to determine the effectiveness of the implementation of education personnel at MAN Pangkep Pangkep Regency and the factors that influence the effectiveness of the influencing the effectiveness of the implementation of education personnel management at MAN Pangkep Pangkep Regency. This research uses descriptive qualitative research. Approach The research approach uses an investigative approach. Data sources are done by purposive which is determined through certain considerations and objectives. The method of data collection was observation, interviews and documentation using research instruments interview guidelines. Data analysis by reducing data, presenting data and providing conclusions or verification. the results showed that the effectiveness of the implementation of education personnel management at MAN Pangkep Pangkep Regency is running well but not yet effective which includes five things, namely the quantity of education personnel at MAN Pangkep Pangkep district, the quality of work of education personnel at MAN Pangkep Pangkep district, the time efficiency of education personnel at MAN Pangkep Pangkep district, the work performance of education personnel at MAN Pangkep Pangkep district and improving the quality of human resources of education personnel at MAN Pangkep Pangkep regency. The supporting factors for the implementation of education personnel management at MAN Pangkep Pangkep Regency lie in the facilities and infrastructure factors, work environment factors, apparatus awareness factors, ability and skill factors and the rules and policies of the madrasah head. While the inhibiting factors lies in the work quantity factor and the uneven HR factor.